Attitudinal commitment in firms' de-internationalization processes. Issue 4 (11th August 2020) - Kuiken, Andrea; Wentrup, Robert; Schweizer, Roger
Abstract : Purpose: This paper aims to examine the de-internationalization process to determine how different forms of attitudinal commitment influence the de-internationalization process. Design/methodology/approach: Because of the exploratory nature of the study, a case study design is used. Two cases of Swedish companies, which de-internationalize from the French market, are studied. Findings: Different commitment profiles influence the de-internationalization process. In particular, a general commitment profile, in which affective, normative, instrumental and continuance commitment play a role, influences the timing of de-internationalization, while the effort directed toward the execution of de-internationalization is mainly influenced by normative commitment and the extent of de-internationalization mainly by instrumental commitment. Research limitations/implications: By offering three propositions regarding the four types of commitment and the effects of these commitment types on the process of de-internationalization, the authors contribute to the literature on de-internationalization and the commitment literature. Practical implications: The findings suggest that there is a risk that managers continue to commit resources to a market for a longer period without clear benefits because of affective and continuance commitment. As local employees persist in committing to the local market because of continuance commitment, offering viable alternatives reduces commitment to the foreign operations. Originality/value: Distinguishing between different types of commitment, the paper builds on a more fine-grained typology of commitment than previous internationalization literature. Thereby, the paper opens up for new insights in the de-internationalization process.